Controlling as a way to continuous improvement - Kruml Lukáš (NYME, 2015)
This paper deals with controlling as one of the most important tools (approaches) of corporate management based on continuous improving. It lays out possibilities for its interconnection with knowledge management and process management as ones of the most important management tools supporting continuous improvement in the knowledge economy and in the so-called knowledge society. Possible relations between controlling, knowledge and process management are examined and described. Their interconnection with the controlling system of a firm multiples its assets in terms of the synergy effect and increases the efficiency of management, creation of innovations and productivity of the entire organization. For these purposes graphic model is created that represents these basic relations and expresses also the principle of continuous improvement, which is considered to be the point of entire controlling as well as of knowledge and process management.
Controlling jako nástroj neustálého zlepšování
Keywords: controlling; continuous improvement; knowledge management; process management; relationships; controlling; neustálé zlepšování; znalostní management; procesní management; vztahy